Acaricidal activity of nishinda (Vitex negundo) leaf and garlic (Allium sativum) bulb extract against red spider mite, Oligonychus coﬀeae (Acari: Tetranychidae) in tea plantations of Darjeeling hill, West Bengal, India - Banerjee, Piu; Laha, Arghya; Samaddar, Indrani; Biswas, Himaniv; Sarkar, Debjani; Roy, Sovan; Saha, Goutam K.; Podder, Sanjoy (Acta Biologica Szegediensis, 2021)
The red spider mite, Oligonychus coffeae (Nietner) serves as a serious threat to the Darjeeling tea plantations affecting the quality of the leaves. Various plant extracts are currently being researched as an alternative to the chemical pesticides to control the red spider mites. In the present study, the leaves of Vitex negundo L. and the bulb of Allium sativum L. were analyzed for their acaricidal activity on the larval, nymphal and adult stages of the mite. Both the extracts were found to have potent activity against red spider mites and may prove to be potential acaricides in future.